Serum fibroblast growth factor 23 levels in chronic kidney disease and its correlation with bio-chemical parameters in chronic kidney disease: a cross sectional comparative study - Anbarasan, Priya; Khanna, Vinoth (International Journal of Advances in Medicine, 2019)
Background: Globally, chronic kidney disease (CKD) is a major public health problem. Fibroblast growth factor (FGF)-23 is a newly recognized phosphatonin secreted by the osteocytes which acts as a key regulator of serum phosphate levels in CKD. In the present study, we aimed to estimate the levels of serum FGF-23 in patients with CKD and to compare them with healthy controls. Also, we aimed to compare the levels of FGF-23 levels with creatinine clearance and kidney size in various stages of CKD. Methods: A cross sectional comparative study was conducted at Thiruvarur Government Medical College hospital in Tamil Nadu. Patients aged between 20 and 65 years with an established diagnosis of CKD and healthy controls were included in the study. Enzyme Immuno-Assay method was followed for the estimation of FGF-23. Spot Urine sample was collected to determine the presence of albumin. Serum levels of glucose, Urea, Creatinine, Electrolytes (Sodium, Potassium), Albumin, Calcium, Phosphorus and Alkaline Phosphatase were measured. Information on kidney size, cortical echogenicity, parenchymal thickness and cortico-medullary differentiation were assessed based on ultrasound abdomen. Results: A total of 45 CKD cases and 45 healthy controls were studied. Mean (SD) age of CKD cases was 54(11) years and that of controls was 46(9.6) years. The mean value of FGF23 in cases was 730.7±492.7 pg/ml and this was higher than that of the control group whose mean value was 39.49±12.47 pg/ml (P<0.05). Mean GFR levels in cases and controls were 23.8 and 113.8 and this difference was statistically significant (P value<0.0001). Among cases, Pearson correlation between serum FGF-23 levels and eGFR, serum albumin was statistically significant and had a negative inverse correlation. Conclusions: The present study demonstrated that serum FGF23 levels were significantly increased in patients with CKD. This increase in serum FGF23 levels were progressive from the early stages to the late stages of CKD.